MEMBANGUN BUDAYA KERJA YANG PRODUKTIF: SEBUAH KAJIAN TEORISTIS - Deby Nuraini; Binta Zulfa Nafisa; Hilma Sri Wahyuni; Ajeng Mutiarananda Wahyuna; Aminah Yasin (Jurnal Ekonomi dan Bisnis, 2024)
The focus of this study is to theoretically examine how work culture, job satisfaction, and work discipline are related. The study uses a literature review method to collect data, which begins by identifying and synthesizing results from previous studies related to the subject. Furthermore, a theme approach was used to investigate the relationships between key variables. According to the results of the study, a productive work culture is strongly influenced by the level of happiness and discipline. One of the important findings of the research is that leaders have a very important role in creating a supportive work environment, and that employees should actively participate in the process of creating such a work environment. However, the shortcoming of this study is the lack of empirical data that supports its theoretical conclusions. As a result, the hypotheses suggested should be tested in various organizational contexts.